Analisis kemampuan komunikasi matematis siswa kelas VII pada materi PLSV ditinjau berdasarkan KAM - Hermawanti; Khisan, Fihinna Choiratun; Amelia, Risma (IKIP Siliwangi, 2024)
The purpose of this study was to analyze students’ mathematical communication abilities in solving a problem in the material of one variable equation. The method used in this study is a qualitative descriptive method by taking the research subjects of class VII junior high school students, totaling 32 students with upper, middle, and lower KAM classifications. To obtain data, the technique used is to analyze test questions based on indicators of communication skills. The results of the first indicator, namely stating daily events in mathematica symbols, were found to be 34% of students, KAM upper students 11 people, middle 7 people, lower 14 people. The second indicator is explaining ideas orally and in writing with pictures, graphs, and algebra, with 3% of students, KAM upper students 1 people, middle 1 people, lower 30 people. The third indicator is connecting real objects, pictures, and diagrams to the mathematical ideas of 16% of students, KAM upper students 5 people, middle 3 people, lower 24 people. Based on the results of the analysis, the indicators of the students’ mathematical communication ability in terms of are still below average so it can be concluded that it is lacking.